NatD promotes lung cancer progression by preventing histone H4 serine phosphorylation to activate Slug expression. Issue 1 (December 2017) - Ju, Junyi; Chen, Aiping; Deng, Yexuan; Liu, Ming; Wang, Ying; Wang, Yadong; Nie, Min; Wang, Chao; Ding, Hong; Yao, Bing; Gui, Tao; Li, Xinyu; et al.
Abstract N-α-acetyltransferase D (NatD) mediates N-α-terminal acetylation (Nt-acetylation) of histone H4 known to be involved in cell growth. Here we report that NatD promotes the migratory and invasive capabilities of lung cancer cells in vitro and in vivo. Depletion of NatD suppresses the epithelial-to-mesenchymal transition (EMT) of lung cancer cells by directly repressing the expression of transcription factor Slug, a key regulator of EMT. We found that Nt-acetylation of histone H4 antagonizes histone H4 serine 1 phosphorylation (H4S1ph), and that downregulation of Nt-acetylation of histone H4 facilitates CK2α binding to histone H4 in lung cancer cells, resulting in increased H4S1ph and epigenetic reprogramming to suppress Slug transcription to inhibit EMT. Importantly, NatD is commonly upregulated in primary human lung cancer tissues where its expression level correlates with Slug expression, enhanced invasiveness, and poor clinical outcomes. These findings indicate that NatD is a crucial epigenetic modulator of cell invasion during lung cancer progression. NatD is an acetyltransferase responsible for N-α-terminal acetylation of the histone H4 and H2A and has been linked to cell growth. Here the authors show that NatD-mediated acetylation of histone H4 serine 1 competes with the phosphorylation by CK2α at the same residue thus leading to the upregulation of Slug and tumor progression.